A multi‐functional anti‐aging moisturizer maintains a diverse and balanced facial skin microbiome - Iglesia, Sofia; Kononov, Tatiana; Zahr, Alisar S. (Journal of applied microbiology, 2022)
Aims To assess the effect of a 28‐day skincare regimen in healthy female subjects on the facial skin microbiome composition and to determine whether the skincare regimen including a gentle cleansing lotion, a multi‐functional anti‐aging moisturizer formulated with prebiotics and postbiotics at skin neutral pH, and bland sunscreen pushed the microbiome to a healthier state and improved skin aging measured by self‐assessment and clinical photography. Methods and Results The study protocol was in accordance with the EU Scientific Committee on Consumer Safety (SCCS) guidance and met all international standards. In all, 25 female subjects between 35 and 65 years old with Fitzpatrick skin types I–VI, moderate crow's feet wrinkles and global face photodamage were enrolled. After 28 days, the skincare regimen improved microbial facial diversity and shifted the microbiota composition when compared to baseline. Conclusions After 28 days, the skincare regimen treatment shifted the distribution of the facial skin microbiome, positively influencing the skin microbiome diversity and balance, to promote long‐term skin health and protect from further skin aging. Significance and Impact of the Study These results suggest that incorporating prebiotics and postbiotics into a skincare regimen may have a positive impact on the facial skin microbiome in healthy women.